Data supporting: 'Downscaling reverse osmosis for single-household wastewater reuse: towards low-cost decentralised sanitation through a batch open-loop configuration' - Thomas, Navya; McAdam, Ewan; Davey, Christopher J. (Cranfield University, 2022)
There is a significant demand for water recycling in low-income countries. However, wastewater infrastructure is primarily decentralised, necessitating the development of affordable household-scale reclamation technology. In this study, a batch open-loop reverse osmosis (RO) system is therefore investigated as a low-cost clean water reclamation route from highly saline concentrated blackwater
Keywords: Decentralised RO'; 'Batch RO'; 'Urine and faeces'; 'Blackwater'; 'Wastewater RO'; 'Wastewater Treatment Processes'